2017
DOI: 10.1186/s12889-017-4449-7
|View full text |Cite
|
Sign up to set email alerts
|

Four-year trends in adiposity and its association with hypertension in serial groups of young adult university students in urban Cameroon: a time-series study

Abstract: BackgroundObesity is a major risk factor for non-communicable diseases (NCDs) and is growing rapidly globally including in sub-Saharan Africa (SSA). We aimed to assess the trend in adiposity markers in Cameroonian university students, and investigated their associations with hypertension.MethodsFrom 2009 to 2012, we annually measured weight, height, blood pressure, waist (WC) and hip circumferences, and calculated the body mass index (BMI) and other indices of adiposity in consecutive students aged 18 years or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 14 publications
(14 reference statements)
6
16
0
2
Order By: Relevance
“…35 A study conducted by Choukem et al found body mass index and central obesity to be independent predictors for hypertension. 28 This was in concordance with our study. Another study conducted by Uchiyama et al among university students also found a significant relationship between overweight or obese category and hypertension among both males and females (p<0.05).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…35 A study conducted by Choukem et al found body mass index and central obesity to be independent predictors for hypertension. 28 This was in concordance with our study. Another study conducted by Uchiyama et al among university students also found a significant relationship between overweight or obese category and hypertension among both males and females (p<0.05).…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of hypertension in this age group found in our study was similar to study by Dores et al 14 prevalence when compared to our study. [22][23][24][25][26][27][28] Similar studies conducted by Al Majed et al and Kanade et al found higher prevalence in this age group. 29,30 The National Health and Nutrition Survey for the year 2012-2013 reports that the prevalence of hypertension in young adults of United States to be 7.3%, this prevalence is also lower than our study.…”
Section: Discussionsupporting
confidence: 70%
“…Concerning the correlation of SBP with BMI, in line with our results, among 2,726 cameroonian aged 18 years or above, Choukem and al (Choukem et al, 2017) showed that each 1 kg/m 2 increase in BMI was associated with an 11% increase in the prevalence of abnormal high blood pressure (p = .013). Note: Data expressed as means ± standard deviation Abbreviations: <, inferior; ≥, superior or equal; BMI, body mass index; DBP, diastolic blood pressure; HR, heart rate.…”
Section: Systolic Blood Pressuresupporting
confidence: 90%
“…The associations of overweight/obesity and some other adiposity indicators with the risk of hypertension were previously reported in substantial cross-sectional and time-series studies [8][9][10][11], and thus losing weight, as one of the non-pharmacological strategies, is commonly recommended to lower BP [3]. Several simple and low-cost adiposity indicators were developed including general adiposity index (body mass index (BMI) and height-adjusted body weight) and central adiposity indicators such as waist circumference (WC), hip circumference, waist-to-hip ratio, waist-to-height ratio, body adiposity index (BAI), and visceral adiposity index (VAI) [7,11,12].…”
Section: Introductionmentioning
confidence: 69%
“…Several epidemiological studies explored the association between VAI scores and risk of hypertension or CVDs but with inconsistent conclusions on the predictive ability of the VAI [10,11,15,25,26,36]. Though the positive association between the VAI scores and the risk of hypertension were demonstrated in different populations, there are still considerable studies that reached differing conclusions.…”
Section: Discussionmentioning
confidence: 99%